2002
DOI: 10.1093/molehr/8.9.789
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin enhances in-vitro invasiveness of breast cancer cell lines by up-regulation of matrix metalloproteases

Abstract: Until recently, relaxin (RLX) has been known predominantly for its effects on the reproductive system, where it induces remodelling of the extracellular matrix and up-regulation of matrix metalloproteases (MMPs). In solid cancers, tissue remodelling and MMP activation are essential for invasion and metastasis. We therefore investigated the effect of RLX on invasiveness and MMP expression of human breast cancer cell lines. Upon incubation with porcine RLX, the invasiveness of SK-BR3 cells was significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 40 publications
4
99
0
3
Order By: Relevance
“…14 -17 Relaxin affects proliferation and differentiation of MCF-7 human carcinoma cells in a concentration-dependent manner 18 and can modify the extracellular matrix by affecting the expres-sion of matrix metalloproteinases (MMPs), which potentially contribute to relaxin's role as a migration-promoting peptide in mammary carcinoma cells of different species, 15 including humans. 19 In the present study, we have for the first time revealed novel roles for RLN2 in human thyroid carcinoma cells. We identified neoplastic thyroid tissues as a source of RLN2 and LGR7, implicating an active RLN2-LGR7 signaling system in human thyroid carcinoma.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…14 -17 Relaxin affects proliferation and differentiation of MCF-7 human carcinoma cells in a concentration-dependent manner 18 and can modify the extracellular matrix by affecting the expres-sion of matrix metalloproteinases (MMPs), which potentially contribute to relaxin's role as a migration-promoting peptide in mammary carcinoma cells of different species, 15 including humans. 19 In the present study, we have for the first time revealed novel roles for RLN2 in human thyroid carcinoma cells. We identified neoplastic thyroid tissues as a source of RLN2 and LGR7, implicating an active RLN2-LGR7 signaling system in human thyroid carcinoma.…”
mentioning
confidence: 56%
“…Relaxin has previously been identified as a hormone promoting the motility of human and canine mammary carcinoma cell lines (human, MCF-7 and SK-BR3; canine, CF33.Mt) 15,32 as well as noncarcinogenic bronchial epithelial cells and inflammatory cells infiltrating wounds. 33, 34 Here we demonstrate that both recombinant RLN2 and secreted proRLN2 profoundly accelerated the cellular motility of two human thyroid carcinoma cell lines (FTC-133 and FTC-238) and the corresponding RLN2 transfectants in an autocrine/ paracrine LGR7-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin zymography was performed as described previously. 10 Briefly, samples were loaded into an 8% zymogram gel copolymerized with 0.1% gelatin under nonreducing conditions. Gels were then washed twice with a 2.5% Triton X-100 solution for 30 min, followed by a 30 min wash in incubation buffer (50 mM Tris-HCl buffer pH 8.0, 5 mM CaCl 2 and 1 lM ZnCl 2 ; pH 8.0).…”
Section: Gelatin Zymographymentioning
confidence: 99%
“…8 However, the regulation of these enzymes by relaxin have also been suggested as a mechanism for its role in facilitating cancer cell migration and invasion. [9][10][11] Although the biological significance of relaxin in the male remains elusive, the prostate gland appears to be relaxin's main source. 8 In the human, there are 3 relaxin alleles encoding 3 hormones, named H1, H2 and H3.…”
mentioning
confidence: 99%